2020
DOI: 10.1016/j.ijid.2020.05.059
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on the COVID-19 pandemic in the USA: Will we be better prepared next time?

Abstract: Reflections on the COVID-19 pandemic in the USA: Will we be better prepared next time?"By failing to prepare, you are preparing to fail." Benjamin Franklin Faced with the threat of the 2019 novel human coronavirus (COVID-19), communities worldwide turn to healthcare systems with expectations of emergency preparedness. The ultimate scope and reach of the current COVID-19 pandemic are unknown. At the time of this writing (May 8, 2020), the COVID-19 toll in the United States of America (US) exceeds 1.2 million in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…In the United States, limited access to testing reagents, inadequate testing capacity at the national and community levels, and fragmented funding have prevented the development of accurate and reliable tests, resulting in a significant number of undiagnosed cases. 60 , 61 Additionally, the initial test kits released by the Centre for Disease Control (CDC) were flawed and took weeks to correct, squandering a critical month during which aggressive and widespread testing might have reduced the speed and scale of the pandemic in the country. 62 Similarly, in Canada, shortages of testing supplies led to backlogs and delayed diagnosis, isolation, and contact tracing.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the United States, limited access to testing reagents, inadequate testing capacity at the national and community levels, and fragmented funding have prevented the development of accurate and reliable tests, resulting in a significant number of undiagnosed cases. 60 , 61 Additionally, the initial test kits released by the Centre for Disease Control (CDC) were flawed and took weeks to correct, squandering a critical month during which aggressive and widespread testing might have reduced the speed and scale of the pandemic in the country. 62 Similarly, in Canada, shortages of testing supplies led to backlogs and delayed diagnosis, isolation, and contact tracing.…”
Section: Resultsmentioning
confidence: 99%
“…While Canada's universal health care program provided free testing and treatment access to all citizens and residents, unprecedented levels of unemployment in the United States left many without health insurance and, therefore, made them less likely to seek testing and care due to the cost. 61 , 64 In response, a new aid package, the Families First Coronavirus Response Act, which included provisions for free testing and paid sick leave for a portion of the population, was developed. 64 Unfortunately, the act was not implemented until March 18, nearly a month after the United States had documented widespread community transmission (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential for devastating bioterror and biological attacks has been heightened by COVID-19, as it is now evident to the world, including America's enemies, that the United States is woefully underprepared for threats of this variety. By underestimating the dangers posed by pandemic diseases and focusing on other, more conventional high-politics issues such as international war, America has demonstrated that it is vulnerable to precisely the kind of damage it is now enduring from COVID-19 (Bearman et al, 2020). As Gronvall (2020) notes, strategic adversaries may conclude from the U.S. response to COVID-19 and the harm it has caused to military readiness and the economy that the same effects could be replicated by a biological attack (p. 81).…”
Section: Discussionmentioning
confidence: 99%
“…To the Editor : Infectious diseases physicians and microbiologists are pivotal in guiding the response to the coronavirus disease 2019 (COVID‐19) pandemic. Their involvement ranges from managing cases and coordinating local responses to establishing timely and accurate diagnostic testing 1,2 . We conducted a survey of infectious diseases physicians and microbiologists in Australia and New Zealand in early March 2020 to assess the impact on workload and the perspectives of infectious diseases physicians in the pre‐pandemic period.…”
mentioning
confidence: 99%